DYNAMICS OF IMMUNOLOGIC INDICES BLOOD OF DOGS UNDER VARIOUS METHODS OF TREATMENT OF WOUNDS - Слюсар, Г. В. (Scientific Progress & Innovations, 2013)
An dynamics of immunological parameters for the different treatment of wounds in dogs. It is shown that topical preparations of hyaluronic acid and tryfuzolu in treatment of purulent wounds in dogs stimulates healing by accelerating reparative processes. Established faster recovery performance of specific and nonspecific resistance of the organism in a phase of regeneration and proliferation of wound healing: increase of T and B lymphocytes, IRI, the number of phagocytic and NBT-test.